Penataan Pertanahan Desa Sidan Berbasis Ekowisata Untuk Pembangunan Berkelanjutan - I Wayan Wesna Astara; Anak Agung Istri Agung; Ni Luh Made Mahendrawati; Putu Ayu Sriasih Wesna; I Wayan Kartika Jaya Utama; Indah Permatasari; I Nyoman Putu Budiartha; I Made Suwitra; I Nyoman Sukandia (Universitas Warmadewa, 2025)
Land management integrated with ecotourism is crucial for sustainable village development in rural Bali, where natural and cultural potential is often hampered by irregular land management, a lack of legal certainty over customary land, and the risk of agricultural land conversion. This community service program aims to address these issues in Sidan Village, Gianyar District, through an ecotourism-based land management approach to optimize tourism potential such as Kissidan Eco Hill while preserving the environment and cultural values. The methods used included land law socialization, the application of digital mapping technology for land inventory and zoning, and sustainability strategies through strengthening village and customary village institutions. Results showed increased community understanding of regulations such as the Basic Agrarian Law (UUPA), the Integrated Land Management System (PTSL), and the LP2B Protection Law, which differentiates between productive agricultural and tourism areas, as well as strengthened synergy between institutions to mitigate the risk of land disputes. Overall, this program successfully established Sidan Village as a model for sustainable ecotourism, balancing economic development, environmental conservation, and local wisdom through orderly and law-based land management.